The origin of Dual System and Vocational Training in Aragón (Spain) - Domingo Cebrián, Virginia (Revista Complutense de Educación, 2017)
The recent implementation of Dual System and Vocational Training has taken place in Aragón, Spain. It is a new educational system which combines lessons at school, where the apprentices study, and the instruction is given by the different companies. This combination of two different institutions makes the system of dual education. Therefore, apprentices must attend classes taught at school while they are also training in a company. This model tries to reduce youth unemployment in Spain and seeks for a closer work and cooperation between companies and schools. Several projects have undergone through the last years in Aragón, helping to create an increasing tendency that echoes others that have taken place in other Spanish communities, as well as in many European countries. The implementation of Dual System and Vocational Training also tries to fulfil the needs most companies have by giving practical training to the apprentices in the same place they can later get a job. Several collaboration agreements are created between the companies and the schools in order to back all these cooperation and make easier the whole process. In the end it’s a pilot project that pretends to join forces and strategies from different areas and participants.
Keywords: Dual vocational training; dual system; professional school; education; Aragón